(untitled) (Analysis in Theory and Applications, 2018)
In this paper, we obtain the boundedness of the parabolic singular integral operator T with kernel in L(L)^1/ γ (S^n−1) on Triebel-Lizorkin spaces. Moreover, we prove the boundedness of a class of Marcinkiewicz integrals μ_Ω,q(f) from \|f\|_F_p^0,q(R^n) into L^p(R^n).